Clinical Benefits of Ketorolac in Postoperative Pain Control Management: A Comprehensive Review - Noer, Tjandrakirana M Sjaifullah; Pribadi, Florence; Dion, Aldy (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Pain accounts for about 70% of visits to emergency rooms, approximately 80% of surgical patients experience acute postoperative pain, more than 38% of patients are readmitted following surgery due to severe pain. Up to 77% of post surgical patients received insufficient pain treatment, following treatment 71% of patients reported continuing to experience pain and 80% said they were still experiencing moderate to severe pain. Previous studies conducted both domestically and internationally have demonstrated the benefits of ketorolac and its usefulness in managing postoperative pain. This article's goal is to provide a comprehensive understanding of the potential of ketorolac as a pharmacological agent in the management of post-operative pain. A narrative review method was employed, utilizing research articles and international guidelines to gather literature. Around 230 libraries were found to meet the criteria and studied, 27 libraries were used in order to create this article. Ketorolac has a good safety profile and there are a few contraindications in patients that clinicians must be aware. Studies suggest that administering ketorolac within two hours after surgery for a treatment duration of two to five days. Numerous studies have demonstrated the potential of ketorolac in the therapy of postoperative pain.